Rosacea with extensive extrafacial lesions - Pereira, TM (2008)
Rosacea is a very common skin disorder in the clinical practice that primarily affects the convex areas of the face. Extrafacial rosacea lesions have occasionally been described, but extensive involvement is exceptional. In the absence of its typical clinical or histological features, the diagnosis of extrafacial rosacea may be problematic. We describe an unusual case of rosacea with very exuberant extrafacial lesions, when compared with the limited involvement of the face.